2020
DOI: 10.3390/antibiotics9070413
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Bioactivity Characterization of Filipin Derivatives from Engineered Streptomyces filipinensis Strains Reveals Clues for Reduced Haemolytic Action

Abstract: The rise in the number of immunocompromised patients has led to an increased incidence of fungal infections, with high rates of morbidity and mortality. Furthermore, misuse of antifungals has boosted the number of resistant strains to these agents; thus, there is urgent need for new drugs against these infections. Here, the in vitro antifungal activity of filipin III metabolic intermediates has been characterized against a battery of opportunistic pathogenic fungi—Candida albicans, Candida glabrata, Candida kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Despite the intrinsic instability and often high toxicity of polyene macrolactams, several derivatives are world-leading drugs in clinical use, such as nystatin (tetraenes), filipins (pentaenes), , and amphotericin B (heptaene). , As the numbers of conjugated double bonds within the polyene macrolides have been presumed to correlate with higher fungicidal activity, we anticipated a similar degree of antibiotic activity of termidomycin A ( 1 ). Indeed, activity studies revealed moderate to good antimicrobial activity against Gram-positive and Gram-negative bacteria and fungi ( Bacillus subtilis , Escherichia coli , Pseudomonas aeruginosa , Mycobacterium vaccae , Sporobolomyces salmonicolor , and Penicillium notatum (Table S5)) in comparison to that of the positive controls ciprofloxacin and amphotericin B.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the intrinsic instability and often high toxicity of polyene macrolactams, several derivatives are world-leading drugs in clinical use, such as nystatin (tetraenes), filipins (pentaenes), , and amphotericin B (heptaene). , As the numbers of conjugated double bonds within the polyene macrolides have been presumed to correlate with higher fungicidal activity, we anticipated a similar degree of antibiotic activity of termidomycin A ( 1 ). Indeed, activity studies revealed moderate to good antimicrobial activity against Gram-positive and Gram-negative bacteria and fungi ( Bacillus subtilis , Escherichia coli , Pseudomonas aeruginosa , Mycobacterium vaccae , Sporobolomyces salmonicolor , and Penicillium notatum (Table S5)) in comparison to that of the positive controls ciprofloxacin and amphotericin B.…”
Section: Resultsmentioning
confidence: 99%
“…First, the acquired metabolic data of strain RB110−1 was searched for the absence/presence of the proposed longer-chain termidomycin congener E (5; Figure 2C, Figures S20−S23 Bioactivity Studies. Despite the intrinsic instability and often high toxicity of polyene macrolactams, several derivatives are world-leading drugs in clinical use, such as nystatin (tetraenes), 42 filipins (pentaenes), 43,44 and amphotericin B (heptaene). 44,45 As the numbers of conjugated double bonds within the polyene macrolides have been presumed to correlate with higher fungicidal activity, we anticipated a similar degree of antibiotic activity of termidomycin A (1).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been used to detect Niemann–Pick type C disease [ 13 ] which is an autosomal recessive lysosomal storage disorder due to mutations in the NPC1 or NPC2 gene that can lead to a fatal disease in neonatal infants or chronic neurodegeneration in adults [ 87 ]. Filipin, similar to other polyenes, has been used to construct semi-synthetic derivatives searching to increase safety [ 88 ].…”
Section: Polyene Structure and Chemical Behaviormentioning
confidence: 99%
“…the presence three vinyl methyls, eight olefinic protons, fourteen oxymethine, and an aminosugar moiety. The The geometry of the three double bonds of the tetraene chromophore has been assigned as 16E, 18E, and 22E-configuraiton based on the large vicinal coupling constants between H-16 and H-17 (J = 14.9 Hz), H-18 and H-19 (J = 15.0 Hz), H-22 and H-23 (J = 13.7 Hz) [21]. The vicinal coupling constant J20,21 could not be detected due to the absence of proton on C-20.…”
Section: Isolation and Structure Elucidationmentioning
confidence: 99%